A 1V 1.4 mW multi-band ZigBee receiver with 64 dB SFDR. (June 2018) - Li, Zhiqun; Yao, Yan; Wang, Zengqi; Cheng, Guoxiao; Luo, Lei
Abstract: A low voltage low power receiver supporting 780/868/915/2400 MHz ZigBee bands is presented in this paper. The receiver exploiting low-IF architecture consists of a RF-to-BB (baseband) current reuse front-end, a Gm-C based variable gain complex band-pass filter (CBPF) for image rejection and four stages of limiting amplifiers which saturate IF signal for demodulation. The proposed ZigBee receiver chip is implemented in TSMC 180 nm CMOS technology with metal-insulator-metal (MIM) capacitors. PCB measurement results show that the receiver has 45.9 dB conversion gain, 8.5 dB NF and −33.5 dBm out-of-band IIP3 at sub-GHz bands. When working in 2.4 GHz band, the gain is 38.4 dB, noise figure (NF) is 16.7 dB and the out-of-band IIP3 is −28.2 dBm. The S11 bandwidth (S11 < −10 dB) can cover the entire ZigBee spectrum (700–2500 MHz). The receiver consumes 1.42 mW from a 1 V DC supply and the die size is 1.41 mm 2 including all pads.